2020
DOI: 10.21303/2504-5571.2020.001130
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation Coefficients Analysis on Innovative Sustainable Development Groups

Abstract: The purpose of this study is to observe the evaluation of all the factors that influence sustainable development, by doing this, the author collected all the logically affecting indicators of 2000–2018 and divided them into 4 groups by affiliation which are Economic and Political, Energy and Environmental, Innovation and Entrepreneurship, Intellect and Social Capital. This paper tries to perform the correlation coefficients matrix analysis to show, how the innovative indicators on sustainable development group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The results were interpreted in accordance with the recommendations published in the work by Turan (2020). For this purpose, the Cheddock scale was used, which defines the following possible options for the strength of the correlation between two variables: − weak -0.1-0.3; − significant -0.3-0.5; − moderate -0.5-0.7; − high -0.7-0.9; − very high -0.9-1.0.…”
Section: "I Am Often Surprised By the Reactions Of Others To What I D...mentioning
confidence: 99%
“…The results were interpreted in accordance with the recommendations published in the work by Turan (2020). For this purpose, the Cheddock scale was used, which defines the following possible options for the strength of the correlation between two variables: − weak -0.1-0.3; − significant -0.3-0.5; − moderate -0.5-0.7; − high -0.7-0.9; − very high -0.9-1.0.…”
Section: "I Am Often Surprised By the Reactions Of Others To What I D...mentioning
confidence: 99%
“…It should be noted that scientists (Grubb et al, 2021;Nemet et al, 2018;Grubler, 2021) emphasize the difference between innovative development in the energy sector from other areas, in particular, the dependence of energy-consuming technologies on energy costs and competition (Butyrskyi et al, 2019) solely on this criterion. Scientists (Lin, Zhu, 2019;Turan, 2020;Brych et al, 2021) argue that the drivers of economic development of the state in terms of energy innovation is the existing innovation potential, which accumulates and is formed taking into account trends in world economies, the dynamics of human capital and exhaustion of natural resources. Numerous studies (Wang, Wang, 2020;Elia et al, 2021;Rubin et al, 2015;Trofymenko et al, 2021;Dluhopolskyi et al, 2021) in the field of energetics have found that the cost of innovative technologies and the speed of their penetration into the market depends on the level of experience and progress of learning in the innovation process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The purpose of the article. This study aims to analyze the data obtained as a result of the combination of 4 main innovative sustainable development groups and indicators developed by the author, based on the UNDP's sustainable development targets, as a result of the multifactorial analysis of the selected indicators between 2000 -2018 years in the energy sector of Ukraine, which is a part of the author's research [12]. Examination and comparison of the energy visions of Europe and Ukraine plus the result that will emerge will contribute to the author's research and will enable companies in the energy sector to look at sustainable development goals from an alternative perspective.…”
mentioning
confidence: 99%